Liquid Metals and Disulfides: Interactive Metal‐Polymer Hybrids for Flexible and Self‐Healable Conductor. Issue 3 (1st February 2021) - Xin, Yumeng; Lou, Yang; Liu, Huaizhi; Wu, Dongfang; Zhang, Jiuyang
Abstract: Growing interests have been received in metal‐polymer hybrid composites for their combined features of metals and polymer. However, the detrimental incompatibility between inorganic and organic polymer matrix makes it challenging to prepare homogenous hybrid composites for advanced applications. This work reports using disulfides, as interactive binding bonds, to interact with liquid metals (LMs) for fabricating the liquid metal‐disulfide (LMDS) composites. The interaction between disulfides and liquid metals lead to uniform dispersion of LM droplets in polymer matrix and strengthen the whole polymer network for improved mechanical performance. Interestingly, this work discovers that the LM droplets could act as efficient initiator to promote the ring‐opening polymerization to obtain the composites. In addition, the interactive LMDS composites exhibit excellent self‐healing ability ascribing to the dynamic LM‐disulfide interaction and disulfide metathesis. The phenomenal electrical conductivity and self‐healing feature enable LMDS composites as stretchable self‐healing conductors with the ability to control the electrical circuits. Abstract : The interactive liquid metal‐disulfide polymer (LMDS) hybrid composites are fabricated by using disulfide bonds as interactive binding bonds for liquid metals (LMs). The interaction between disulfides and LMs enable uniform dispersion of LM droplets and improve mechanical performance. The interactive LMDS composites can serve as self‐healable conductors for flexible circuit and electronic switch to control the circuits under on/off pressure.